Evaluación de la sustentabilidad de un proceso de transición agroecológica en sistemas de producción hortícolas familiares del partido de La Plata, Buenos Aires, Argentina - Flores, Claudia C. (2015)
From the point of view of agroecology, sustainability is achieved through a process of agroecological transition to rationalize the use of resources and involve farmers in technology generation. One of the main troubles to advance the transition is the lack of methodologies to assess these processes. The aim of this work was to evaluate, through the use of indicators developed specifically for this target, the changes in the sustainability of an agro-ecological conversion experience with a group of horticultural farmers in La Plata, Argentina, during the first three years of the agro-ecological transition process. We worked with a group of seven horticultural farmers. A set of sustainability indicators was developed. These indicators were measured at baseline and after 3 years into the transition. At the same time, a participatory assessment was performed to detect the most sensitive problems from farmer’s point of view. The use of indicators, early in the process, allowed detecting many critical points, mostly linked to the agrochemical’s use. Meanwhile, participatory assessment revealed that the more sense problem was pests. To solve the problems participatory trials were conducted in order to contrast conventional practices with those based on agroecological principles. The evaluation of the results helped to identify appropriate for solving problems and promote agro-ecological approach learning technologies. Thus, progress was made in the redesign of production systems to changing technologies more environmentally friendly inputs for process technologies, which contribute to the quality of products and the preservation of health. The aim of this study was to: promote a transition process with a group of farmers in La Plata and develop a methodology to assess whether this process improves sustainability. The evaluation of the transition process, after 3 years into the job, said the sustainability of these systems was improved.